1992
DOI: 10.1007/bf01647655
|View full text |Cite
|
Sign up to set email alerts
|

Can proctological procedures resolve perianal pruritus and mycosis?

Abstract: Twenty-three patients with pruritus ani associated with anal mycosis underwent primary treatment of a concurrent anal disorder. The anal disorders included haemorrhoids (n = 9), fissure (n = 8), anal spasm without fissure (n = 5), and occult mucosal prolapse (n = 1). Pretreatment investigation of faeces for parasites was negative. The glucosal tolerance test and white blood cell count were normal in all cases. Culture of skin smears from the perianal region was positive for Candida only in 16 patients, Dermato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 6 publications
0
6
0
2
Order By: Relevance
“…In these cases, anal mycosis may resolve after treatment of the underlying proctologic disease. 5 Fungal cultures can help specify the type of mycotic infection and help differentiate it from other infectious etiologies. The culture is obtained from scrapings of the scaly portions of the lesion and performed on Sabouraud glucose agar.…”
Section: Mycotic Infectionsmentioning
confidence: 99%
“…In these cases, anal mycosis may resolve after treatment of the underlying proctologic disease. 5 Fungal cultures can help specify the type of mycotic infection and help differentiate it from other infectious etiologies. The culture is obtained from scrapings of the scaly portions of the lesion and performed on Sabouraud glucose agar.…”
Section: Mycotic Infectionsmentioning
confidence: 99%
“…It is recommended to treat of all co-existing a norectal conditions [13,14] . Pironeet al suggested that surgery for benign anorectal conditions can eliminate perianal fungal infection and both measures together reduce pruritus [16] .…”
Section: Anorectal Disordersmentioning
confidence: 99%
“…Thus, any variations in the anal anatomy that produce soiling can be responsible for perianal dermatitis. 3 Grade III and grade IV hemorrhoids and anal tags, polyps, fissures, and fistulas are causes of overt soiling and are evident upon dermatologic examination. 4 Contrarily, internal mucosal-hemorrhoidal prolapse, another cause of occult soiling, stays in the anal canal and cannot be seen through external inspection; it can be diagnosed only with a complete proctologic examination, which includes proctoscopy.…”
Section: Persistent Perianal Dermatitis Associated With Mucosal Hemormentioning
confidence: 99%